Islam Hadhari as a State Policy in Responding to Religious Violence and Terrorism - Othman Talib,; Badlihisham Mohd Nasir, (Institut Islam Hadhari Universiti Kebangsaan Malaysia, 2010)
Islam Hadhari (Civilisational Islam) that emerged after the landslide victory of Barisan Nasional in 2004 has become a very popular in Malaysia. It is noticed that Islam Hadhari is a newly promoted concept that could be applied as the state policy to govern Malaysia in the modern era. It is also a continuous approach of Penerapan Nilai-nilai Islam (Inculcating Islamic Values) that was firstly introduced by Tun Mahathir Mohamad in 1980s. As far as the government of ruling party is concerned, Islam Hadhari is the concept that promotes Islam in a most subtle approach for the contemporary Malaysia. Since it had been immediately promoted after the September 11 2001, the concept could also be considered as the best policy in responding to religious violence in all over the world. As a nation that used to experience difficulties in establishing peace and harmony among the multi-racial society, the concept is believed to be the modern way in applying Islamic policy within the Malaysian society. The paper would firstly discuss about the need of Malaysia for the policies in preserving peace and harmony. Secondly it would study the concept of Islam Hadhari as understood by the government particularly in the light of responding to the religious violence. A brief evaluation of the effectiveness of the policy would be finally discussed in the paper